Methods of Evaluating Exploxive Reactivity of Explosive-Contaminated Solid Waste Substances - T S. Bajpayee; Richard J. Mainiero (International Society of Explosives Engineers, 1988)
The Bureau of Mines, U.S. Department of the Interior, has developed test procedures and criteria for evaluating explosive reactivity of explosive contaminated solid waste substances generated by U.S. Army Ammunition Plants. These substances are produced as explosive-contaminated sludge from waste water treatment plants, residues from the burning of munitions and explosives on open ground, and residues from deactivation furnaces. The characterization of explosive reactivity is a prerequisite for disposal of such waste materials, which may be contaminated with primary explosives, propellants, or pyrotechnic materials. The Bureau has proposed two tests for this purpose. These tests were developed to evaluate the explosive reactivity as defined in Title 40, Code of Federal Regulations, Part 261.23(a)(6) and (7). These are Bureau of Mines Gap and Bureau of Mines Internal Ignition tests, which determine the sensitivity to shock and thermal stimuli, respectively. This paper also includes gap and internal ignition reference data for typical blasting agents, high explosives, propellants, and marginally reactive substances. These reference data were used to establish test criteria. The Bureau has evaluated over 400 samples of contaminated soil, sludge, and burning residues using these two test methods.